2005
DOI: 10.3844/ajassp.2005.1389.1394
|View full text |Cite
|
Sign up to set email alerts
|

Flow of Dividends under a Constant Force of Interest

Abstract: This study addresses the issue of maximization of dividends of an insurer whose portfolio is exposed to insurance risk. The insurance risk arises from the classical surplus process commonly known as the Cramér-Lundberg model in the insurance literature. To enhance his financial base, the insurer invests in a risk free asset whose price dynamics are governed by a constant force of interest. We derive a linear Volterra integral equation of the second kind and apply an order four Block-byblock method of Paulsen e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…To find the survival probabilities φ(u), we took advantage of the fourth-order block-by-block method in conjunction with Simpson's Rule of integration to solve the VIE (18). This method, which produces solutions in blocks of two values, is fully developed in [39] and appears in several papers, e.g., [5,38,49]. Linz [36] has shown that the block-by-block method always converges and has an order of convergence of four (see also [51]).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find the survival probabilities φ(u), we took advantage of the fourth-order block-by-block method in conjunction with Simpson's Rule of integration to solve the VIE (18). This method, which produces solutions in blocks of two values, is fully developed in [39] and appears in several papers, e.g., [5,38,49]. Linz [36] has shown that the block-by-block method always converges and has an order of convergence of four (see also [51]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the literature, two-, three-and four-block block-by-block methods have been used to solve Volterra integral equations (e.g., [36] for non-linear VIE-2s, [37] for a system of linear VIE-2s). More recently, Kasozi and Paulsen [38] used the two-block block-by-block method to study the flow of dividends under a constant interest force. They derived a linear VIE-2 and applied a fourth-order block by-block method of Paulsen et al [39] in conjunction with Simpson's rule to solve the Volterra integral equation for the optimal dividend barrier.…”
Section: Introductionmentioning
confidence: 99%
“…However, not many of these address the dividend optimization problem using numerical methods. Kasozi and Paulsen (2005a) used the block-byblock numerical method to study the flow of dividends under a constant force of interest. Their study culminated into a linear Volterra integro equation of the second kind.…”
Section: Introductionmentioning
confidence: 99%
“…The integral equations with Cauchy kernel have been widely used in solving problems associated with aerodynamic, hydrodynamic and elasticity (Lifanov, 1996;Ladopoulos, 2000;Abdou and Naser, 2003;Mohankumar and Natarajan, 2008;Lara and Mariagrazia, 2005;Kasozi and Paulsen, 2005a;Kasozi and Paulsen, 2005b;Ganji et al, 2008;Thukral, 2005).…”
Section: Introductionmentioning
confidence: 99%